Odd one out - Stone, Nic (Crown, 2018)
High school juniors and best friends Courtney and Jupe, and new sophomore Rae, explore their sexuality and their budding attractions for one another
Keywords: Friendship; Dating (Social customs); Sexual orientation; High schools; Schools; Freundschaft; Verlieben; High school; Konflikt; USA; Jugendbuch